Carbapenemase-producing Aeromonas species isolated from the urban-impacted Akaki river in Ethiopia. (1st June 2022) - Yitayew, Berhanu; Woldeamanuel, Yimtubezinash; Asrat, Daniel; Aseffa, Abraham; Olsson, Per-Erik; Mihret, Adane; Jass, Jana
Abstract: Carbapenemase-producing Aeromonas species are an emerging health threat. This study aimed to determine carbapenemase-mediated resistance among Aeromonas isolates from the Akaki river, Ethiopia during the dry and wet seasons in 2019–2020. Antimicrobial susceptibility to carbapenems and cephalosporins was determined and carbapenemase production was confirmed. Of 163 isolates, the majority were human pathogens Aeromonas caviae (62), Aeromonas hydrophila (33) and Aeromonas veronii (49). These isolates were resistant to carbapenem and cephalosporin antibiotics, with the highest resistance to cefotaxime 86 (59.7%), ertapenem 71 (49.3%) and imipenem 65 (45.1%). Resistance to carbapenem antibiotics varied between species, where most A. veronii 37 (75.5%) and A. hydrophila 28 (84.8%) were resistant to imipenem and all A. caviae were sensitive. A. veronii, A. caviae and A. hydrophila resistance to meropenem was 31 (63.3%), 3 (4.8%) and 19 (57.6%), respectively. Of isolates resistant to carbapenem, 82.1% A. hydrophila and 94.4% A. veronii were carbapenemase producers. Cephalosporin resistance also varied among the different species. The highest resistance to carbapenem antibiotics was in isolates collected during the wet season ( p <0.05); however, it was not consistent across all classes of antibiotics tested. The rivers in megacities could be reservoirs of carbapenemase-producing Aeromonas spp. HIGHLIGHTS: Carbapenem-resistant Aeromonas species were found in an urban-impacted river. Different Aeromonas species had different resistance levels to carbapenems. Resistance was mediated by carbapenemases in A. veronii and A. hydrophila . Seasonal variation affected the distribution of carbapenem-resistant Aeromonas in aquatic environments. Graphical Abstract